Simulation and Validation of Thickness of Slag Crust on the Copper Stave in the High-Temperature Area of Blast Furnace - Dongliang Liu; Wei Zhang; Zhengliang Xue; Chunhui Song; Lingkun Chen (Metals, 2023)
The blast furnace is the dominant high-temperature reactor in the modern ironmaking industry. Iron oxide in iron ores can be converted to metallic iron through blast furnace smelting, and this high-temperature melting can be used to separate the molten iron from the gangue components. The formation and thickness of the hot-surface slag crust on the copper stave in the high-temperature area of the middle and lower parts of the blast furnace are crucial for the safe operation and long campaign of the blast furnace. To enhance the precision of determining the thickness of the slag crust in this specific region, samples were extracted from the hot surface of the copper cooler situated in the high-temperature area. This extraction was carried out during the maintenance procedure of the blast furnace stockline. Subsequently, the thermal conductivity and melting performance of the slag crust were measured. The slag crust thicknesses corresponding to the various temperature measurement sites of the stave were determined by developing a mathematical model for the heat transfer of the copper stave. The actual slag crust thickness measurement data were acquired while the blast furnace stockline was in operation, and the data were then utilized to corroborate the model’s predictions. A blast furnace with an effective volume of 3200 m3 was used to test the model. The average thickness of the hot-surface slag crust was computed for cases that occurred between 2020 and 2022. The data’s correlations with the blast furnace’s technical and economic indices during the same time period were examined. The findings indicated that the blast furnace’s operation indices improved with a thinner slag crust, but there was also a higher chance of damage to the copper stave’s internal cooling water pipes. Taking into account the technical and economic indices as well as a long campaign of the blast furnace, 150–200 mm is recommended as the appropriate average slag crust thickness on the surface of the copper stave in the high-temperature section.